Sustainable Lithium Battery Development in Indonesia: The Role of Natural Materials and Recycling Processes in Future Challenges - Latif, Chaironi; Yogianto, Mohammad Fahmi Ilmi; Hafidz, Isa; Adziimaa, Ahmad Fauzan (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2025)
The development of sustainable lithium-ion batteries is essential to meet the global demand for efficient, high-capacity, and environmentally friendly energy storage systems. This study reviews recent advancements in lithium battery technologies in Indonesia, emphasizing the utilization and performance of locally available natural materials. Among various lithium-ion battery types, those based on Lithium Nickel Manganese Cobalt Oxide (NMC) and Lithium Iron Phosphate (LFP) are considered the most promising for Indonesia due to the availability of key raw materials such as nickel, cobalt, and iron. Additionally, various battery recycling techniques—including pyrometallurgy, hydrometallurgy, bio-hydrometallurgy, and direct recycling methods—are systematically analyzed for their effectiveness in material recovery and environmental impact mitigation. The findings highlight the need for integrated strategies that combine local material utilization, innovation in battery materials and recycling technologies, environmental stewardship, and supportive regulatory frameworks to accelerate the development of a sustainable lithium-ion battery ecosystem in Indonesia.